2017
DOI: 10.1080/15287394.2017.1357370
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to decabromodiphenyl ether (BDE-209) produces mitochondrial dysfunction in rat liver and cell death

Abstract: Polybrominated diphenyl ethers (PBDE) are ubiquitous environmental pollutants. Exposure to these chemicals has been associated with developmental neurotoxicity, endocrine dysfunctions, reproductive disorders, and hepatotoxicity. The widespread use of PBDE as flame retardants has culminated in daily exposure of humans and wildlife to these contaminants and resulted in their banned use. Thus assessment of the potential effects of each PBDE congener on living organisms has become cause for concern. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 70 publications
(88 reference statements)
1
7
0
Order By: Relevance
“…Although our previous results have shown autophagic induction [39,40], persistent mitochondrial damage may have led these cells to death by apoptosis elicited by different stimuli, to culminate in phosphatidylserine exposure and nuclear condensation and fragmentation. Anthropogenic chemicals and other stressors can impact macromolecular mitochondrial structures via molecular interference or mechanical damage [22].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although our previous results have shown autophagic induction [39,40], persistent mitochondrial damage may have led these cells to death by apoptosis elicited by different stimuli, to culminate in phosphatidylserine exposure and nuclear condensation and fragmentation. Anthropogenic chemicals and other stressors can impact macromolecular mitochondrial structures via molecular interference or mechanical damage [22].…”
Section: Discussionmentioning
confidence: 63%
“…We have recently published that BDE-153 and other congeners can cause genomic instability, as revealed by comet assay results obtained after exposure to BDE-153 at 5, 10, or 25 μM for only 4 h [38]. In addition, we have shown the same compound can induce HepG2 cell autophagy [39,40] in an attempt to save cells from the damage caused by BDE-153. Autophagy is a pro-survival process that occurs under stressful conditions, such as xenobiotics impact [29].…”
Section: Discussionmentioning
confidence: 92%
“…According to previous studies, BDE-209 exhibits toxicity to plants and animals, posing emerging risks to humans and ecosystems via the food chain (Hu et al 2010, Ji et al 2017, Pereira et al 2017, Li et al 2018. PBDEs have been detected in human tissues (Cai et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The induced effects of xenobiotics related to DNA damage and apoptosis have been well investigated by in vitro or ex vivo studies. For example, previous studies indicated that different PBDE congeners including BDE‐47 and BDE‐153 induced mitochondrial damage, genetoxicity, and apoptosis in rat liver and HepG2 cells 25‐29 . However, in vivo studies, the DNA damage and apoptosis induced by PBDEs still need to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies indicated that different PBDE congeners including BDE-47 and BDE-153 induced mitochondrial damage, genetoxicity, and apoptosis in rat liver and HepG2 cells. [25][26][27][28][29] However, in vivo studies, the DNA damage and apoptosis induced by PBDEs still need to be further explored.…”
mentioning
confidence: 99%